Value-Based Leadership in Public Partnering Projects: A Qualitative Study from Norway - Omar K. Sabri; Mikkel Timberlid (Buildings)
One of the emerging forms of cooperation in managing government projects is partnering (samspill) to address repetitive problems in large projects. Inefficiency, conflict, and cost volatility remain work issues in the public sector. Although risk sharing and incentive schemes are other aspects of partnering that are the subject of a significant amount of research, there is limited investigation into the softer aspects of partnering. The nature of partnering and how it is practiced depends on various components, such as trust, leadership, and culture; however, they are not well defined or appreciated. This paper investigates how these soft aspects are implemented and perceived in four mega Norwegian public construction projects that use a partnering model. In the present study, a qualitative research approach was adopted, and nine face-to-face interviews were conducted with project leaders from four case organizations in public sector healthcare, government, and education sectors. However, despite having similar contractual provisions, the projects exhibited varying degrees of collaboration success, indicating that formal agreements alone do not determine effective partnering. The outcomes from this study established that value-based leadership is central to the success of collaboration and should, therefore, be a priority when designing partnering in the public sector. Additionally, the results add to the existing debates regarding the application of soft values in the formal structures of the business and support the notion of leadership-based approaches in construction management, especially in the public domain.